THE URGENCY OF EMBEDDING RELIGION-BASED LITERACY FOR FUTURE MOSLEM’S INTELLECTUALS - Choirul Muna; Puji Lestari; Fatma Isnaeni (Edusoshum : Journal of Islamic Education and Social Humanities, 2022)
One of the fields that is a benchmark for the progress of a nation is education. The world of education is one of the most logical paths towards an advanced future. Therefore, the world of education must have the proper guidelines so that the learning process can run effectively and efficiently. The Method used in this study is a literature review, namely by conducting a comprehensive literature review of previous relevant studies, then analyzing the concepts developed. The results of the study state that the primary thing that becomes a reference so that future generations can become intellectuals and be able to think critically is through Literacy. Formal education provides a reading culture system in the learning curriculum with the support of the environment and adequate facilities. Meanwhile, non-formal education starts from family education which is based on Islam. Thus, it is hoped that it can positively impact the Indonesian nation, especially the Muslim generation, in readiness to face life in the next era. In order to be able to compete in the global world and build a new civilization, it is undoubtedly better than the previous civilization, namely with a moderate and dignified civilization.